2018
DOI: 10.1038/s41467-018-05057-z
|View full text |Cite
|
Sign up to set email alerts
|

Giant antidamping orbital torque originating from the orbital Rashba-Edelstein effect in ferromagnetic heterostructures

Abstract: Enhancing the in-plane current-induced torque efficiency in inversion-symmetry-breaking ferromagnetic heterostructures is of both fundamental and practical interests for emerging magnetic memory device applications. Here, we present an interface-originated magnetoelectric effect, the orbital Rashba–Edelstein effect, for realizing large torque efficiency in Pt/Co/SiO2/Pt films with strong perpendicular magnetic anisotropy (PMA). The key element is a pronounced Co 3d orbital splitting due to asymmetric orbital h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…These results may be related to the OT, which requires further investigation. Finally, we remark that the orbital angular momentum can be generated not only by the OHE but also by the interfacial Rashbatype states [36,37], which may be related to sizable field-like torque measured in Py/(Cu)/AlO x structure [38]. References S10…”
Section: Note That the Relative Ratio Between Smentioning
confidence: 99%
“…These results may be related to the OT, which requires further investigation. Finally, we remark that the orbital angular momentum can be generated not only by the OHE but also by the interfacial Rashbatype states [36,37], which may be related to sizable field-like torque measured in Py/(Cu)/AlO x structure [38]. References S10…”
Section: Note That the Relative Ratio Between Smentioning
confidence: 99%
“…On the other hand, in the case of Pt(O)/NiFe/SiO 2 with heavily oxidized Pt, the observed dominant DL SOT is attributed to an intrinsic SOT arising from the Berry curvature at the interface 23 . In addition to conventional REE, the combined effect of enhancement in orbital moment and spin-orbit coupling was also proposed to account for the sign reversal of DL SOT in Pt/CoFeB(O)/MgO below temperature of 200 K 20 , and significant enhancement in DL torque in Pt/Co/SiO 2 29 . The oxygen may also modify the charge and spin transport property at the interface, e.g ., it was reported that spin-mixing conductance of Co/CoO x /Pt is enhanced due to antiferromagnetic nature of CoO x 21,22 , and the spin Hall angle in Pt is increased by weakening of proximity effect 22 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the CISP, we study the polarization of the atomic orbital angular momentum, called the current-induced orbital polarization (CIOP), which acts on the spin as an effective magnetic field through the LS coupling. The CIOP was recently studied in crystals [70][71][72][73], and the orbital current was also calculated in the orbital Hall effect in crystals [74][75][76][77] and in the orbital filter in a model of CISS [78]. Here we calculate both CIOP and CISP as a function of the radius and the pitch of the helix in the linear response to the chemical-potential difference between source and drain electrodes in the Landauer approach.…”
Section: Introductionmentioning
confidence: 99%